Cationic local composition fluctuations in rapidly cooled nuclear fuel melts. (June 2022) - Jizzini, Mohamed; Brackx, Emmanuelle; Piluso, Pascal; Menut, Denis; Guinebretière, René
Graphical abstract: Highlights: We demonstrate through high-resolution X-ray diffraction experiments that large cationic fluctuations are present inside the corium crystals similar to those appearing during the Fukishima Daiichi reactor severe accident. Abstract: During a severe accident in a nuclear reactor, as it occurred in Fukushima Daiichi BWRs in 2011, the so-called "corium" resulting from the thermal fusion of nuclear fuel and interaction with the zircaloy cladding at high temperature (T > 2800 K) can be formed. During cooling phases in the vessel or outside of the vessel, corium is crystallized at solid state under the form of an uranium and zirconium oxide solid solution. Based on the severe accident scenario, different phenomena can occur such as Fuel Coolant Interaction (FCI). In those conditions, solidification paths will be far from thermodynamic equilibrium if the corium is cooled very quickly by interacting with water. At the CEA-Cadarache, on the PLINIUS Severe Accident Platform, FCI is studied at the KROTOS experimental facility using prototypical corium, i.e. with depleted uranium dioxide. Resulting from different stages of corium - water interaction, we hypothesis that a large cationic composition fluctuation takes place into these U1-x Zrx O2±y crystals. Thanks to high-resolution X-ray diffraction experiments done at the SOLEIL synchrotron radiation source at the MARS beamline, we were able to analyze at the quantitative level the cationic composition fluctuations that are strongly related to the cooling speed.